Manejo de neumonía por sars-cov-2 en adultos varones - Rojas Jiménez, Julio Andrés (Machala: Universidad Técnica de Machala, 2023)
Introduction: Pneumonia due to SARS-CoV-2 infection is particularly worrying due to its ability to severely affect the lungs and cause severe symptoms in a significant percentage of patients Objective: Establish the management of pneumonia SARS-CoV 2, to provide better health care. Methodology: We conducted searches in academic and scientific databases, such as PubMed, Google Scholar and Scielo, using search terms such as "Covid-19", "SARS-CoV-2", "pneumonia", "management", "treatment". We selected articles published in indexed journals during the period from 2018 to 2023, which specifically address the management of SARS-CoV-2 pneumonia. Development: In the management of SARS-CoV 2 pneumonia, patients with SaO2 oxygen saturation equal to or less than 92-93% and signs of polypnea, oxygen therapy and the decubitus prono have been shown to be effective in the early stages of disease and steroid use in patients with 92% SaO2. Remdesivir was shown to shorten recovery time in hospitalized patients with low respiratory infection due to VOCID-19; however, its impact on mortality has not been decisive. Management of the excessive inflammatory response associated with COVID-19, known as cytokine storm, is addressed with therapies such as Tocilizumab, an IL-6 inhibitor, and corticosteroids. Conclusion: Management varies according to the severity of the disease. Patients with mild pneumonia may be treated in outpatient settings or at home, while moderate or severe cases should be hospitalized.
Introducción: La neumonía debido a infección del SARS-CoV-2, es particularmente preocupante debido a su capacidad para afectar gravemente los pulmones y causar síntomas graves en un porcentaje significativo de pacientes. Objetivo: Establecer el manejo de la neumonía SARS-CoV 2, para brindar una mejor atención en salud. Metodología: Se llevó a cabo búsquedas en bases de datos académicas y científicas, como PubMed, Google Académico y Scielo, utilizando términos de búsqueda como "COVID-19", "SARS-CoV-2", “neumonía”, "manejo", "tratamiento". Se seleccionaron artículos publicados en revistas indexadas durante el período comprendido entre 2018 y 2023, que aborden específicamente el manejo de la neumonía SARS-CoV-2. Desarrollo: En el manejo de neumonía SARS-CoV 2, pacientes con saturación de oxígeno SaO2 igual o menor al 92-93% y signos de polipnea, la oxigenoterapia y el decúbito prono se han mostrado efectivos en las etapas iniciales de la enfermedad y el uso de esteroides en pacientes con SaO2 ≤ 92%. El Remdesivir demostró acortar el tiempo de recuperación en pacientes hospitalizados con infección respiratoria baja por COVID-19; sin embargo, su impacto en la mortalidad no ha sido determinante. El manejo de la respuesta inflamatoria excesiva asociada con la COVID-19, conocida como tormenta de citoquinas, se aborda con terapias como el Tocilizumab, un inhibidor de la IL-6, y corticoides. Conclusión: El manejo varía según la gravedad de la enfermedad. Los pacientes con neumonía leve pueden ser tratados en entornos ambulatorios o en el hogar, mientras que los casos moderados o graves deben ser hospitalizados.
Keywords: COVID-19 VIRUS; SARS-COV-2 VIRUS; CORONAVIRUS; TRATAMIENTO FARMACOLÓGICO